Risk factors of heterotopic ossification in traumatic spinal cord injury Fatores de risco da ossificação heterotópica na lesão medular traumática - Cláudia Virgínia C. Coelho; Paulo Sergio S. Beraldo (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Heterotopic ossification (HO) is a complication of the spinal cord injury (SCI). It can result in anchylosis, harming the rehabilitation and quality of life. Previous publications had not elucidated the relation between possible independent variables, the aim of this study. METHOD: From 230 patients with SCI, admitted in 1998 at Hospital SARAH Brasilia, 33 with HO (14.3%; CI95% 10.1-19.6) were compared with 33 controls. The risk factors had been tested in bivariate analysis and in a model of logistic regression. RESULTS: Spasticity (odds ratio=3.8; CI95% 1.15-12.30), number of pressure ulcers (2.1; CI95% 1.08-3.89) and time lapsed since the injury (1.1; CI95% 1.02-1.24) were independently associated with HO. There was a confounder effect among these variables, without interaction. CONCLUSION: Spasticity, pressure ulcer and time of injury are associated with HO in spinal cord injury. The first two factors can be prevented and treatable. OBJETIVO: A ossificação heterotópica (OH) é uma complicação da lesão medular traumática (LMT). Pode resultar em anquilose, prejudicando a reabilitação e a qualidade de vida. Estudos prévios não elucidaram a relação entre as potenciais variáveis independentes, propósito desse estudo. MÉTODO: De 230 pacientes com LMT, admitidos em 1998 no Hospital SARAH Brasília, 33 tiveram o diagnóstico de OH (14,4%; IC95% 10,1-19,6), que foram comparados a 33 controles. Os fatores de risco foram testados de forma bivariada e num modelo de regressão logística. RESULTADOS: Espasticidade (razão de chances 3,8; IC95% 1,15-12,30), número de escaras (2,1; 1,08-3,89) e tempo de lesão (1,1; 1,02-1,24) encontraram-se associadas, de forma independente, à presença de OH. Havia um efeito confundidor entre essas variáveis, porém sem interação. CONCLUSÃO: Espasticidade, escaras e tempo de lesão estão associados à OH na lesão medular traumática. Os dois primeiros são passíveis de prevenção e tratamento.